Blocking PERK resuces vascular smooth muscle cells from homocysteine-induced ER stress and apoptosis - Wei Li; Fujun Shang; Xiaoli Li; Shaoping Lu; Xiaolin Niu; Zhimin Zhang; Jing Liu; Xue Li; Lianyou Zhao (Frontiers in Bioscience-Landmark, 2020)
Hyperhomocysteinemia induces stress response in endoplasmic reticulum (ERS). Here, we tested whether blockage of homocysteine (Hcy) induced ERS and subsequent apoptosis in vascular smooth muscle cells can be inhibited by blockage of PERK/eIF2α/ATF4/CHOP signaling. Short-term exposure of vascular smooth muscle cells to Hcy led to the phosphorylation of PERK (pPERK), which in turn, phosphorylated eIF2 alpha (peIF2α) and inhibited the unfolded protein response. Long-term Hcy exposure, however, increased the expression of ATF-4 and CHOP and led to apoptosis. Treatment of cells with salubrinal, a specific inhibitor for eIF2α decreased the expression of ATF-4 and CHOP, and prevented apoptosis. Together, the results show that PERK pathway is involved in Hcy-induced vascular smooth muscle cell apoptosis and that blocking the PERK pathway protects against this injury.